The Inequitable Effects of Raising the Retirement Age on Blacks and Low-Wage Workers. Issue 1 (March 2019) - Moore, Kyle; Ghilarducci, Teresa; Webb, Anthony
Increasing the Social Security Full Retirement Age (FRA) adversely affects all workers because an increase is equivalent to an across-the-board cut in benefits. Raising the FRA leaves workers with two bad choices: working longer or living on reduced monthly benefits for the rest of their lives. Working longer further penalizes Blacks and low-wage workers because they are unlikely to live long enough to recoup payments foregone as a result of delayed claiming. Instead of cutting Social Security benefits, retirement policy makers should update and modernize the 401(k) and IRA systems to provide workers with better options.